The influence of different environmental factors toward Vietnam's net-zero emissions goal - Asif Raihan; Mohammad Ridwan; Tapan Sarker; Filiz Guneysu Atasoy; Grzegorz Zimon; ABM Mainul Bari; Md Shoaibur Rahman; Hayat Khan; Babla Mohajan (Innovation and Green Development)
Emissions of greenhouse gases (GHGs), especially carbon dioxide (CO2), have an impact on the global climate, posing risks to environmental sustainability. Vietnam's economic growth and agricultural development have led to higher utilization of energy and emissions. Analyzing the trade-off between pollution and development in Vietnam can help mitigate environmental degradation while achieving Vietnam's goal of net-zero emissions by 2050. The research empirically investigates the effects of the economy, energy, technology, agriculture, and forestry on Vietnam’s environmental quality. The study analyzed yearly data from 1990 to 2020 using the dynamic ordinary least squares (DOLS) technique. Empirical results show that as the economy and energy use rise, so do pollution. Conversely, a rise in technological innovation, agricultural productivity, and forest cover would reduce Vietnam's emissions. The stability of the DOLS results is observed when operating the canonical cointegrating regression (CCR) afterward fully modified least squares (FMOLS) techniques. To achieve its net-zero emissions goals and gain sustainable development, Vietnam should switch to cleaner energy, adopt low-carbon economies, encourage green technology innovation, use climate-smart farming methods, and reduce deforestation.